Composition, fatty acids profile, oxidative stability, and acceptance of meat from broiler chickens fed acerola (Malpighia emarginata) meal-enriched diets - de Oliveira, Joselaine [UNESP]; Landim de Barros, Thainá [UNESP]; Pires, Helenice Aparecida [UNESP]; Pereira, Raquel de Cássia [UNESP]; Pereira Cassiano, Rodrigo [UNESP]; Garcia-Neto, Manoel [UNESP]; Giglio Ponsano, Elisa Helena [UNESP] (Taylor & Francis, 2023)
The large production of broilers and fruits in Brazil demands the exploration of new sources of nutrients for the birds and of sustainable disposal of the fruit industrialization wastes. The effects of feeding broiler chickens with residues from acerola industrialization (AM) on meat composition, fatty acids profile, oxidative stability and sensory characteristics were evaluated. Four soybean-corn based diets were tested: negative control, with no antioxidant nor AM; positive control, with butyl hydroxytoluene (BHT) and no AM; and two diets containing either 5 or 7.5% AM and no antioxidant. Official validated methods were used for the chemical and sensorial analyses of the meat. On breast, 7.5% AM increased protein (14.13%) and ash (10.6%) concentrations. On both cuts, AM reduced around 30% the cholesterol levels, decreased saturated fatty acids, increased polyunsaturated fatty acids and reduced n-6:n-3. AM at 5% delayed the onset of lipid peroxidation in frozen stored breasts more than did the antioxidant BHT (36 x 22.5 days). Breasts from treatment containing BHT had the worst sensorial acceptance by consumers. The addition of acerola meal to broiler chickens’ diets revealed a good option to provide healthier meat with longer shelf life, besides representing a way of reducing fruit waste in the environment.
Keywords: acerola; broiler chicken; lipid peroxidation; lipid profile; meat quality